Description of Energy Adequacy for Workers at PT. Indotec Tiga Putra Kupang City - Virgine Angelina Tinggogoy; Noorce Ch. Berek; Agus Setyobudi (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The minimum energy requirement for Indonesian people in the 2019 AKG is 2,100 kcal per person per day, so each person must have a minimum energy intake of 2,100 kcal per day. If the food intake is not sufficient for needs, it can result in disruption of the body's immunity, reduced body weight, reduced physical ability, work slowly and even decreased work productivity. This research aims to determine the description of energy adequacy of workers at PT. Indotec Tiga Putra Kupang City 2022. This type of research is quantitative research using a descriptive approach. This research used a total sampling of 24 workers. The research instruments used were 2x24 hour food recall, 2x24 hour physical activity recall, microtoise and digital scales, food photo books and nutrisurvey applications. The results showed that respondents with light physical activity (83.3%), adequate intake of breakfast (54.2%) and dinner (70.8%), lunch intake (62.5%), morning snack and afternoon (66.7%) which is less. The level of energy adequacy is in the poor category (58.3%). The results of this study also show an average energy expenditure of 3,521.6 kcal and energy income of 2,691.4 kcal. It is recommended that workers consume food sources of energy in sufficient quantities/portions.